2021
DOI: 10.1002/ece3.7523
|View full text |Cite
|
Sign up to set email alerts
|

A deep dive into fat: Investigating blubber lipidomic fingerprint of killer whales and humpback whales in northern Norway

Abstract: In cetaceans, blubber is the primary and largest lipid body reservoir. Our current understanding about lipid stores and uses in cetaceans is still limited, and most studies only focused on a single narrow snapshot of the lipidome. We documented an extended lipidomic fingerprint in two cetacean species present in northern Norway during wintertime. We were able to detect 817 molecular lipid species in blubber of killer whales ( Orcinus orca ) and humpback whales ( Megaptera nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 87 publications
(152 reference statements)
1
10
0
Order By: Relevance
“…These studies performed the first comprehensive characterization of the lipid profile of the plasma, 166,167 heart, 168 and adipose tissue (i.e., blubber). 169 Lipidomics can be applied as a diagnostic tool to screen the metabolic and physiological conditions of marine mammals. Understanding lipidome fluctuations between health and sick organisms contributes to uncovering metabolism alterations, helping in the identification of sick animals.…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
See 3 more Smart Citations
“…These studies performed the first comprehensive characterization of the lipid profile of the plasma, 166,167 heart, 168 and adipose tissue (i.e., blubber). 169 Lipidomics can be applied as a diagnostic tool to screen the metabolic and physiological conditions of marine mammals. Understanding lipidome fluctuations between health and sick organisms contributes to uncovering metabolism alterations, helping in the identification of sick animals.…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
“…A comparative lipidomic study using the blubber of two whale species (Orcinus orca and Megaptera novaeangliae) suggested that differences in the blubber lipidomic fingerprints were triggered by their contrasted This journal is © The Royal Society of Chemistry 2022 life-history strategies, but lipidomic similarities were also found due to their phylogenetic association. 169 Additionally, the authors combined lipidomic and isotopic ratio analyses to identify intraspecific dietary specializations in the killer whale (Orcinus orca) population. The results clustered the killer whales into two different groups according to their diets.…”
Section: Lipidomics Of Marine Vertebratesmentioning
confidence: 99%
See 2 more Smart Citations
“…lipid profile) and blood parameters related to metabolism [135]. As such, lipidomics shows great promise to assess the change in energy body reserves and thus body condition in free-ranging cetaceans [99,133,140,141]. Other omics approaches such as proteomics and metabolomics are also emerging as novel methods to increase our understanding of cetacean metabolism [137,[142][143][144][145].…”
Section: Measuring Health In Cetaceans: Current and Novel Approachesmentioning
confidence: 99%